(untitled) (International Seven Journal of Multidisciplinary, 2024)
Introduction: During pregnancy and childbirth, HIV (the virus that causes AIDS), as well as syphilis and hepatitis B, can be transmitted to the fetus. HIV can also be transmitted during breastfeeding. Aim: The aim of this study was to identify the evidence on prophylactic measures against vertical transmission of HIV between the pregnant woman and the fetus. Material and Methods: The methodology used was a literature review. The research was carried out through an electronic search of scientific articles published on the Scielo (Scientific Electronic Library Online) and Lilacs (Latin American Health Sciences Literature) and Pubmed websites. Results: Cases of HIV-positive pregnant women are increasing every year. This is a consequence of the recent increase in the number of people contracting the HIV virus. Even with all the progress that science has made over the last few decades, cases of mother-to-child transmission of HIV still occur. A few years ago, if a pregnant woman was carrying the virus, her unborn child would inevitably have it. Nowadays, with technology and new procedures performed on pregnant women, the fetus has the possibility of being born free of contamination and having a normal life, which is why early diagnosis and treatment are so important for the health of the newborn. Conclusion: Early treatment in the prenatal period ensures that the child is completely safe. Among the procedures are, at the time of delivery, clearing the newborn’s airways so that the mother’s fluids do not enter the baby’s body. With prenatal diagnosis, early treatment can be started, which can reduce the vertical transmission of HIV and other STIs from mother to fetus, guaranteeing a completely healthy pregnancy and birth.